PENGARUH TANGGUNG JAWAB DAN LOCUS OF CONTROL DALAM KEPUTUSAN INVESTASI POURING GOOD MONEY AFTER BAD - Jesica Handoko (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
Sometimes, a manager (agent) must make difficult decisions like to decide whether to continue or to commit resources to a risky and highly uncertain project (to escalate it), or to abandon it, after a great deal of corporate investment, and possibly personal commitment and reputation, have already been used up. In agency theory perspectives, this decision could be done when there must be a condition of information asymmetry, and an incentive for manager to shirk.This study try to strenghten manager’s responsibility variable and to explore locus of control variable in the relationship with pouring good money after bad investment decision. 95 undergraduate students participate in this study and not found significant results for the alternative hypotheses. It’s suggested that undergraduate students weren’t ready for investment decision researchs, especially when dealing with risky projects, because of their lack of knowledge and experiences.